EVALUASI PENGELOLAAN DANA BANTUAN OPERASIONAL KESEHATAN DI PUSKEMAS III DENPASAR SELATAN DAN JARINGANNYA DI DENPASAR, BALI - Paul, Andrew; Januraga, Pande Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021DO - 10.24843/ACH.2021.v08.i03.p04, 2022)
ABSTRACT The Government has assisted Puskesmas (the Public Health Center) and its networks through the Health Operational Assistance aids. The purpose of this study was to examine the benefits of the funds were received by Puskesmas and felt by the community. This research using qualitative methods through profound interviews with staffs of Puskesmas as well as with several users who used the Puskesmas services. The benefits in terms of management are to support promotive preventive activities and to expand the scope of the program. Then the fulfillment of funding sources for activities. Afterwards the Maternal and Child Health activities and Immunization can run well. The benefit from an operational perspective is can reach the society through activities outside Puskesmas. The benefit for the community in terms of service quality is an increase in service. In terms of ease of access is that the queue is no longer too long. It is also much better in term of privacy because more rooms are available for doing examintaion. Further, the Puskesmas hopes the operational technical instructions for aid funds can be updated. For all staff to keep maintain the good service even to improve it. Keywords: Health Operational Assistance Funds, Promotive and Preventive, Benefit